Manifestowanie religijności przez konfederatów barskich - Głowacki, Jerzy Józef (Acta Universitatis Lodziensis. Folia Historica, 2010)
The issue of the Confederation of Bar, 1768-1772, has interested many historians who dealt with Polish-Lithuanian Commonwealth. It has been commonly considered that the religion played an outstanding role in the Confederation although the religions factor itself has not been a subject of research yet. The present article is the first attempt to describe the Confederates’ religiosity, although it concerns only the external side of the phenomenon. The author brings up such questions like: the symbols of the Confederation and it’s ceremonial. He establishes, the religiosity of the confederates was a continuation of Old Polish customs. The confederates emphasized their attachment to the tradition, especially during the first half of the first year of the confederacy, because they wanted to dissociate from their political adversaries, whom they defined as the enemies of the catholic faith. In some cases it is possible to affirm that religious banners were used by the confederation manipulatively.